Social problems - Best, Joel (W.W. Norton & Company, 2017)
Updated with nine new end-of-chapter case studies and more than 50 new boxed examples, the Third Edition of Joel Best's Social Problems elucidates the complex, competitive process through which social problems emerge, paying particular attention to how resources and rhetoric affect each stage of the process. Drawing on social constructionist theory, Best shows how activists, experts, and their opponents engage in claimsmaking, and how the media then report on these claims, prompting public reaction and driving policy. In order to help students connect theory to everyday life, Joel Best fills the book with colorful examples and real-world case studies